MODEL PEMBELAJARAN LATIHAN KONJUNGSI BAHASA JERMAN MENGGUNAKAN SATZKARTEN: Model Pembelajaran Latihan Konjungsi Bahasa Jerman Menggunakan Satzkarten - Adhima, Fauzan (Paramasastra : Jurnal Ilmiah Bahasa Sastra dan Pembelajarannya, 2022)
This study aims to develop the stages of learning German conjunction grammar exercises using the Satzkarten game. The method used in this research is qualitative with literature study techniques. The Satzkarten game is a German sentence card game that is combined using the right conjunction.The conjunctions chosen in the learning model using the Satzkarten game are aber, oder, denn, deshalb, und on the theme "Tourism" in class XII SMA. Thus students would be able to create and compile German sentences with conjunctions related to vacation or tourist activities. The results of the research on the conjunction training learning model using the Satzkarten game can be applied into three stages of learning. Three stages of learning are carried out, namely (1) Opening Stage, (2) Competency Formation Stage in which there is a Satzkarten game stage, namely Vorbereitungsphase (game preparation), Spielphase (playing), and Auswertungsphase (game assessment), and (3) Closing Stage. The Satzkarten game media in this study can be used by the teacher to train students in practicing conjunctions.The learning steps in this study are presented in the Learning Implementation Plan (RPP). The Satzkarten game in this learning model can be used by the teacher as a technique and alternative media to deliver German conjunction grammar training materials. Keywords: Learning model, German conjunction, Satzkarten games